Stress and genetics influence hair cortisol in FMR1 premutation carrier mothers of children with fragile X syndrome. (July 2021) - Hong, Jinkuk; Kapoor, Amita; DaWalt, Leann Smith; Maltman, Nell; Kim, Bryan; Berry-Kravis, Elizabeth M.; Almeida, David; Coe, Christopher; Mailick, Marsha
Abstract: To investigate genetic and environmental influences on cortisol levels, mothers of children with fragile X syndrome (FXS) were studied four times over a 7.5-year period. All participants (n = 84) were carriers of the FMR1 "premutation", a genetic condition associated with impaired HPA axis functioning. Genetic variation was indicated by expansions in the number of CGG (cytosine-guanine-guanine) repeats in the FMR1 gene (67–138 repeats in the present sample). The environmental factor was cumulative exposure to adverse life events during the study period. Cortisol was measured at the beginning of the study via saliva samples and at the end of the study via hair samples; hormone values from these two specimen types were significantly correlated. The interactions between CGG repeat number and adverse life events significantly predicted hair cortisol concentration, including after accounting for the initial salivary cortisol level. For those with fewer CGG repeats, stress exposure was associated with elevated cortisol, the expected response to stress, although women with a higher number of CGGs had a reduced cortisol response to adverse events, which might be related to HPA dysfunction. These results indicate that both exogenous and endogenous factors affect HPA functioning in this population of women. Highlights: Stress and genetics interact to predict hair cortisol in FMR1 premutation carriers. The premutation is defined as 55–200 CGG repeats in the FMR1 gene. Women with larger numbers of CGG repeats have more impaired HPA functioning. Women with fewer repeats have the expected elevated cortisol in response to stress. Hair and salivary cortisol are correlated over time in FMR1 premutation carriers.